Age‐dependent male mating tactics in a spider mite—A life‐history perspective. Issue 20 (22nd September 2016) - Sato, Yukie; Rühr, Peter T.; Schmitz, Helmut; Egas, Martijn; Blanke, Alexander
Abstract: Males often fight with rival males for access to females. However, some males display nonfighting tactics such as sneaking, satellite behavior, or female mimicking. When these mating tactics comprise a conditional strategy, they are often thought to be explained by resource holding potential (RHP), that is, nonfighting tactics are displayed by less competitive males who are more likely to lose a fight. The alternative mating tactics, however, can also be explained by life‐history theory, which predicts that young males avoid fighting, regardless of their RHP, if it pays off to wait for future reproduction. Here, we test whether the sneaking tactic displayed by young males of the two‐spotted spider mite can be explained by life‐history theory. We tested whether young sneaker males survive longer than young fighter males after a bout of mild or strong competition with old fighter males. We also investigated whether old males have a more protective outer skin—a possible proxy for RHP—by measuring cuticle hardness and elasticity using nanoindentation. We found that young sneaker males survived longer than young fighter males after mild male competition. This difference was not found after strong male competition, which suggests that induction of sneaking tactic is affected by male density. Hardness and elasticity of the skin did not vary with male age. Given that earlier work could also not detect morphometric differences between fighter and sneaker males, we conclude that there is no apparent increase in RHP with age in the mite and age‐dependent male mating tactics in the mite can be explained only by life‐history theory. Because it is likely that fighting incurs a survival cost, age‐dependent alternative mating tactics may be explained by life‐history theory in many species when reproduction of old males is a significant factor in fitness. Abstract : Life‐history theory predicts that young males use nonfighting tactics to compete for females if that increases their lifetime reproductive success. Here, we test this theory using the two‐spotted spider mite, which shows age‐dependent male mating tactics, by comparing male survival between sneaker and fighter males. Also, we show that the hardness of males' outer skin does not change with age, ruling out this factor in age‐dependent male mating tactics.